Backup with Storage in a Database - S. M. Taranin (Моделирование и анализ информационных систем, 2016)
This paper presents an overview of some technologies that are used in modern backup systems. We consider their advantages and disadvantages. Next, we consider an example of the realisation of the backup system with files store in the database. We propose to divide the copied files into blocks of fixed length. Each block is a sequence of bytes. The block length may be adaptive, i.e. it can vary depending on the type or file size. We can store the file content in one table, and information of them such as names, attributes, and relationships between them, store in another table. The information of retained files and folders can be stored also on the client side in a hierarchical structure. It is a set of records and a model of the copied directory. The presence of such a model allows to find changes of the copied directory without additional queries to the database. If a file is modified, it is copied only the changed blocks. The model is also updated on the client side. Thus, the load on the data channel reduces. This paper presents the algorithms of saving and restoring data, and describes the factors that affect to the speed of their work. It demonstrates the dependence of the rate of saving and recovery of the fineness of the partition files, as well as the structure of the copied directory.